Consumers’ Preferences for Different Fish Groups in Tripura, India - Debnath, Biswajit; R.S., Biradar; S.K., Pandey; P.S., Ananthan; Das, Apu; P.R., Patil (Fishery Technology, 2025)
Consumers’ preference for fish in Tripura is facing an interesting dynamism where consumers are supplied with variety of fish species or groups. Preferences for different fish depend on the relative importance given to various attributes of fish and the utility received from it. This paper aims at finding the consumers’ preferences towards various consumption attributes for different fish groups in Tripura. The study was conducted for five selected fish groups across five selected consumption attributes for rural and urban Tripura separately. Local carps, inter-state carps, local non-carps, inter-state non-carps and small weed fish were the five major fish groups identified in fish markets of Tripura. Conjoint analysis of consumption attributes showed 34.08% (for rural Tripura) and 29.72% (for urban Tripura) of relative importance to ‘price’ among five selected attributes (price, taste, availability, freshness and source). ‘Freshness of fish’ was found to be the important consumption attribute for interstate carps and non-carps. Utility profile was found to be the highest for small weed fish (total utility = 31.06) in rural and for local carps (total utility = 35.08) in urban Tripura among five selected Choice Fish Groups. The difference in utility profile between rural and urban may be due to the combination of different factors like higher average income in urban area and greater availability of small weed fish in rural water resources. High income urban consumers have higher purchase power to buy high priced local carps. Boosting up local fish production to reduce the price of fish using ‘principle of supply’ is one of the major strategic options suggested in this study.